Factors Associated with Community Behavior in Complying with Health Protocols during COVID-19 Pandemic in 2022: Study on Community of Liliba Village, Oebobo District, Kupang, East Nusa Tenggara - Jon Kristyson Baitanu; Rina Waty Sirait; Dominirsep O Dodo (Journal of Health Promotion and Behavior, 2023)
Background: Facts show that Liliba Village is one of the health service outreaches in the form of prevention and control of the coronavirus (COVID-19) which truly needs cooperation between the government and health sector, state defense and security sectors such as the Indonesian National Arm Force and the National Police as well as participation from the community. Without good cooperation between the government and related agencies and participation from the community, the spread of the coronavirus (COVID-19) cannot be controlled, causing adverse impacts on the community. This study aims to determine the factors related to community behavior in complying with health protocols during the COVID-19 pandemic in Liliba Village, Oebobo District, Kupang City in 2022. Subjects and Method: This was a cross-sectional study conducted in Liliba Village, Oebobo District, Kupang City, East Nusa Tenggara, from June 2021 to November 2022. A total of 268 subjects were selected for the study. The dependent variable was community behavior. The independent variables were knowledge, attitudes, actions, confidence, beliefs, discipline, facilities and infrastructure, and COVID-19 vaccines. The data were collected using questionnaires and checklists and analyzed using the Chi-square test. Results: Good knowledge (OR= 0.23; 95% CI= 0.08 to 0.62; p= 0.002), positive action (OR= 0.48; 95% CI= 0.40 to 0.57; p= 0.039), high confidence (OR= 0.11; 955 CI= 0.10 to 0.43; p= 0.012), discipline (OR= 0.21; 95% CI= 0.21 to 0.57; p= 0.019), availability of facilities and infrastructure (OR= 0.34; 95% CI= 0.20 to 0.34; p= 0.002), and have complete COVID-19 vaccines (OR= 0.24; 95% CI= 0.10 to 0.54; p= 0.003) were significantly related to community behavior in complying with the health protocols during the COVID-19 pandemic. Conclusion: Good knowledge, positive actions, high confidence, discipline, availability of facilities and infrastructure, and having complete COVID-19 vaccines were related to community behavior in complying with health protocols during the COVID-19 pandemic. Keywords: behavior, compliance, health protocols, pandemic, COVID-19 vaccines. Correspondence:Jon Kristyson Baitanu. Public Health Study Program, Faculty of Public Health, Universitas Nusa Cendana Kupang. Jl. Adisucipto Penfui, Kupang, East Nusa Tenggara, Indonesia. Email: johnbaitanu50@gmail.com. Mobile: +62 8133 9754 645.